Senate Bill 928 Opposition Letter and Responses - A. E. Jewell::::::; Donald R. McNeil::::::; Omer L. Rains:::::: (1975)
A letter to Congress strongly opposing a senate bill which would authorize the sale of property purchased for a State College in Ventura County.